Analyzing And Mapping of Sound Pressure Level in The Packing Plant Unit of PT Semen Padang Teluk Bayur - Ryansyah, Kenan Muhammad; Lestari, Resti Ayu; Bachtiar, Vera Surtia; Serlina, Yega; Latif, Mhd Talib (Jurnal Rekayasa Kimia & Lingkungan, 2025)
The cement industry is one of the strategic industries that has positive and negative impacts. One of the negative impacts is noise pollution. This research aimed to compare the sound pressure level (SPL) to the standard, analyzed the meteorological influence on SPL, and conducted noise level mapping. The noise measurement according to SNI 7231 of 2009. The SPL data was collected by using a Sound Level Meter at 36 points. Additionally, questionnaires were distributed to workers at the PT Semen Padang Teluk Bayur Packing Plant Unit. Measurement of noise used the grid method with sampling points spaced 20-40 meters apart, then analyzed the correlation and influence of meteorological on SPL, and noise mapping with Surfer 27. The results showed that the highest SPL came from the compressor engine at 85.7 dBA, and the lowest SPL was in the office area at 58.1 dBA. The SPL in this study was influenced by meteorological conditions such as temperature, air humidity, wind speed, and air pressure. There was a correlation between temperature and SPL with a value (r) of 0.9936 (very strong) and a correlation between air humidity and SPL with a value (r) of 0.9962 (very strong).